2012
DOI: 10.3109/01443615.2012.704436
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study of the risk of adverse perinatal outcomes due to tuberculosis during pregnancy

Abstract: We conducted a case-control study at three main inner-city hospitals in Birmingham, UK between 2004 and 2006, to determine the risk of adverse perinatal outcomes in pregnant women with tuberculosis (TB) (n = 24), compared with healthy pregnant controls (n = 72). The incidence of TB was 62/100,000 pregnancies, with 54.2% cases having pulmonary TB (41.7% extra-pulmonary; 4.2% both). Infants of mothers with TB had a significantly lower mean birth weight compared with controls (2,735 g vs 3,135 g; p = 0.03). Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 16 publications
3
24
0
2
Order By: Relevance
“…Pregnant women with pulmonary tuberculosis have higher odds of PTB (Asuquo et al, 2012). In a stillbirth where the mother had an upper respiratory infection of F. nucleatum , the bacterium was isolated from the placenta and the infant, and the same clone was identified in her subgingival plaque, but not in the vagina or rectum (Han et al, 2010).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Pregnant women with pulmonary tuberculosis have higher odds of PTB (Asuquo et al, 2012). In a stillbirth where the mother had an upper respiratory infection of F. nucleatum , the bacterium was isolated from the placenta and the infant, and the same clone was identified in her subgingival plaque, but not in the vagina or rectum (Han et al, 2010).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Therefore a high index of suspicion and early referral and diagnosis is recommended. 43 It is crucial to rule out TB infection in new-borns whose mothers have been diagnosed with TB, and this investigation should be performed at the time of delivery. Diagnosis of neonatal TB may be perplexing, and the diagnostic delay may have irreversible consequences for the infant.…”
Section: Risk For Congenital Tbmentioning
confidence: 99%
“…4 A new case-control study conducted in UK showed a lower birth weight in infants born to mothers with TB, especially if pulmonary disease, despite receiving standard treatment. 5 Maternal TB is a risk factor for child TB. Congenital TB is rare, 6 but the risk of transmission to the infant in the postpartum period is higher due to inhalation of aerial droplets coughed out by the mother.…”
Section: Maternal Tuberculosis and Pregnancy Outcomesmentioning
confidence: 99%